Análisis de las cuentas incobrables y su afectación en la liquidez de la compañía de Taxi UTB - Perez Montoya, Nimsi Isabel (2021)
The main reason that directs us to carry out this work has to do with the uncollectible accounts that the UTB Taxi Company has, in order to determine its consequence on liquidity This in order to apply the necessary corrective measures, which allows us to have the necessary information provided by the financial statements. Knowing the financial situation for any company is very important because this way the entity can determine and evaluate all the movements that have been made and all the elements that participate in its operation. That is why it is necessary to adapt to reality when taking into account the multiple tools that exist to carry out a financial analysis. The work is focused on uncollectible accounts since they are the main asset of the UTB Taxi Company, in order to know the affectation that this leads to the liquids of the organization we will use; Liquidity ratios of accounts receivable, average collection period and sale period per day to determine how long the delay in the payments of the respective monthly payments has increased compared to one year with another year 2019 - 2020, we will obtain the respective timely information of the financial statements such as the statement of financial position and income statement.